2008
DOI: 10.1634/stemcells.2008-0346
|View full text |Cite
|
Sign up to set email alerts
|

Improved Efficiency and Pace of Generating Induced Pluripotent Stem Cells from Human Adult and Fetal Fibroblasts

Abstract: It was reported recently that human fibroblasts can be reprogrammed into a pluripotent state that resembles that of human embryonic stem (hES) cells. This was achieved by ectopic expression of four genes followed by culture on mouse embryonic fibroblast (MEF) feeders under a condition favoring hES cell growth. However, the efficiency of generating human induced pluripotent stem (iPS) cells is low, especially for postnatal human fibroblasts. We started supplementing with an additional gene or bioactive molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
217
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(226 citation statements)
references
References 33 publications
7
217
0
2
Order By: Relevance
“…The SV40 large T antigen (T) and the catalytic subunit of human telomerase, hTERT, have been reported to significantly improve the efficiency of generating iPS cells [23,24]. Therefore, we attempted to establish ovine iPS cell lines by adding SV40 large T and hTERT.…”
Section: Generating Sheep Ips Cell Lines Using a Tet-on Inducible Lenmentioning
confidence: 99%
“…The SV40 large T antigen (T) and the catalytic subunit of human telomerase, hTERT, have been reported to significantly improve the efficiency of generating iPS cells [23,24]. Therefore, we attempted to establish ovine iPS cell lines by adding SV40 large T and hTERT.…”
Section: Generating Sheep Ips Cell Lines Using a Tet-on Inducible Lenmentioning
confidence: 99%
“…The first evidence for a role of p53 in the control of this process came from studies on human fibroblasts in which either SV40 large T antigen (a repressor of p53 and pRb pathways) [24] or p53 small interfering RNA (siRNA) [25] were used together with the Yamanaka factors to improve the efficiency of iPSC reprogramming. Subsequently, it was demonstrated that inhibition or loss of p53 increases reprogramming efficiency by 3-to 10-fold, depending on the cell system or the manner of deletion or inactivation of p53 [22,23,[26][27][28].…”
Section: Opinionmentioning
confidence: 99%
“…Suppression of the p53 pathway may compromise a cell's genome stability. For instance, adding SV40 large T into the reprogramming mix accelerated the speed of iPSC formation; however, many of the iPSCs gained chromosomal abnormality (Mali et al, 2008). Thus, during reprogramming, one must take extra care to maintain the intricate balance between safeguarding genome integrity and change of cell fate.…”
Section: Overcoming the Dna Damage Responsementioning
confidence: 99%